Direct Conversion of Activated 5‐Hydroxymethylfurfural into δ‐Lactone‐Fused Cyclopentenones. Issue 2 (21st December 2018) - Gomes, Rafael F. A.; Coelho, Jaime A. S.; Afonso, Carlos A. M.
Abstract: Valorization of biomass derived feedstock (e.g., 5‐hydroxymethylfurfural platform) is a very active field of chemical research. In this study, 5‐hydroxymethylfurfural is converted into cyclopenten‐2‐ones by virtue of furfural's activation and Meldrum's acid's tendency to undergo decomposition/esterification. Experimental and computational studies suggest a domino rearrangement–lactonization reaction involving BINOL‐catalyzed lactonization as the rate‐determining step. The novel lactone‐fused cyclopenten‐2‐ones, which bear a quaternary carbon and resemble a didemnenone natural product structure, are converted into several derivatives with potential interest for the fields of synthetic and medicinal chemistry. Abstract : Meldrum‐atic : Several value‐added cyclopentenones bearing a quaternary carbon center were prepared from biomass‐derived 5‐hydroxymethylfurfural (HMF) by condensation with 2, 2‐dimethyl‐1, 3‐dioxane‐4, 6‐dione (Meldrum's acid) followed by a ring‐opening–cyclization–lactonization cascade process.